Composite catalyst as well as preparation method and application thereof

By using composite catalysts, including MOFs materials and doped iron and cobalt atoms, combined with the electrofenton sewage treatment method, the problem of difficulty in removing PAEs in the environment is solved, and efficient PAEs degradation and good catalyst stability are achieved.

CN119565606APending Publication Date: 2025-03-07GUIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411044017.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove phthalates (PAEs), one of the common endocrine disturbance substances in the environment. Due to their ease of migration, difficulty in degradation and biotoxicity, it has been restricted in use in many countries but still cannot be completely eliminated.

Method used

A composite catalyst is provided, including a MOFs material and iron atoms and cobalt atoms doped in the MOFs material, contacting the sewage containing organic pollutants by an electrofenton sewage treatment method, and conducting an electrofenton catalytic reaction to remove PAEs.

Benefits of technology

The composite catalyst can significantly reduce the toxicity of the catalytic degradation product, improve cycle stability, and the degradation rate of DMP reaches 93.1% within 5 hours, showing good catalytic activity and environmental adaptability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565606A_ABST
    Figure CN119565606A_ABST
Patent Text Reader

Abstract

The invention provides a composite catalyst and a preparation method and application thereof, the composite catalyst is of a cubic crystal structure, and the composite catalyst comprises an MOFs material and iron atoms and cobalt atoms doped in the MOFs material. The composite catalyst is wide in pH application range, high in catalytic activity and high in cycling stability, and the toxicity of catalytic degradation products can be obviously reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental functional materials, and specifically relates to a composite catalyst and a preparation method and application thereof. Background Art

[0002] Phthalates (PAEs) are endocrine disruptors, colorless, non-volatile and water-soluble synthetic organic compounds. PAEs can improve the strength, hardness, plasticity and durability of materials, so they are often widely used in various industrial production such as plastics, pesticides, cosmetics, etc. According to statistics from information processing services, the annual global consumption of PAEs in 2021 exceeded 3.5 million tons, of which China is the world's largest plasticizer consumer market. Because PAEs are non-polar molecules and are not covalently bound to the polymer molecules in plastics, they can easily migrate out of the product and be released directly or indirectly into various environments. For example, PAEs have been detected in soil, sediments, rivers, seawater and the atmosphere.

[0003] PAEs are weakly bound to polymers, so they are easily released from products and migrate into the environment. Currently, PAEs can be detected in the atmosphere, soil, and water environments. For example, PAEs contained in landfills can migrate to groundwater through rainwater and landfill leachate; in addition, PAEs are also quite abundant in the air, and are directly exposed to it through human respiration; even PAEs discharged from factories and urban wastewater can accumulate in organisms through drinking water or the food chain. It is reported that the concentration of PAEs detected in domestic wastewater ranges from 1μg / L to 100μg / L. PAEs are one of the endocrine disruptors. When humans are exposed to them for a long time, they will not only cause reproductive system abnormalities, but also cause neurological and immune diseases, and even cancer. Due to their easy migration, difficulty in degradation, and biological toxicity, PAEs are restricted in use in many countries such as China, South Korea, the United States, and the European Union, but they cannot be completely eliminated. Therefore, there is an urgent need for a suitable treatment method to completely remove them from the environment. Summary of the invention

[0004] In order to solve the deficiencies in the prior art, the present invention provides a composite catalyst and a preparation method and application thereof.

[0005] In a first aspect of the present invention, a composite catalyst is provided. The composite catalyst has a cubic crystal structure and includes a MOFs material and iron atoms and cobalt atoms doped in the MOFs material.

[0006] According to some embodiments of the composite catalyst of the present invention, the pore size of the composite catalyst is 3-20 nm, for example, 3 nm, 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm.

[0007] According to some embodiments of the composite catalyst of the present invention, the specific surface area of ​​the composite catalyst is 150-250m 2 / g; for example, 150m 2 / g, 153.619m 2 / g, 156m 2 / g, 158m 2 / g, 160m 2 / g, 175m 2 / g, 178m 2 / g, 183m 2 / g, 188m 2 / g, 190m 2 / g, 200m 2 / g, 211m 2 / g, 218m 2 / g, 223m 2 / g, 250m 2 / g.

[0008] According to some embodiments of the composite catalyst of the present invention, the specific surface area of ​​the composite catalyst is 154-225m 2 / g.

[0009] According to some embodiments of the composite catalyst of the present invention, the specific surface area of ​​the composite catalyst is 153.619-223.26m 2 / g.

[0010] According to some embodiments of the composite catalyst of the present invention, the pore volume of the composite catalyst is 0.2-0.5 cm 3 / g; for example 0.2cm 3 / g, 0.25cm 3 / g, 0.257cm 3 / g, 0.261cm 3 / g, 0.289cm 3 / g, 0.301cm 3 / g, 0.332cm 3 / g, 0.353cm 3 / g, 0.361cm 3 / g, 0.371cm 3 / g, 0.383cm 3 / g, 0.389cm3 / g, 0.390cm 3 / g, 0.4cm 3 / g, 0.45cm 3 / g, 0.5cm 3 / g.

[0011] According to some embodiments of the composite catalyst of the present invention, the pore volume of the composite catalyst is 0.25-0.4 cm 3 / g.

[0012] According to some embodiments of the composite catalyst of the present invention, the pore volume of the composite catalyst is 0.257-0.392 cm 3 / g.

[0013] According to some embodiments of the composite catalyst of the present invention, the MOFs material is a zeolite imidazolate framework structure material.

[0014] As a typical metal-organic framework (MOF), imidazolide frameworks (ZIFs) have the advantages of stable chemical structure, simple synthesis, easy modification and environmental friendliness. In the ZIFs family, zinc-based imidazolate framework (ZIF-8) is considered to be a promising ZIFs material.

[0015] According to some embodiments of the composite catalyst of the present invention, the zeolite imidazolate framework structure material is ZIF-8.

[0016] According to some embodiments of the composite catalyst of the present invention, the molar ratio of the MOFs material to the iron atom is 64:(0.8-1.2); for example, 64:0.8, 64:0.9, 64:1, 64:1.2.

[0017] According to some embodiments of the composite catalyst of the present invention, the molar ratio of the MOFs material to cobalt atoms is 64:(0.8-1.2); for example, 64:0.8, 64:0.9, 64:1, 64:1.2.

[0018] According to some embodiments of the composite catalyst of the present invention, the molar ratio of the iron atoms to the cobalt atoms is 1:(0.8-1.2); for example, 1:0.8, 1:0.9, 1:1, 1:1.2.

[0019] The second aspect of the present invention provides a method for preparing the composite catalyst according to the first aspect of the present invention, comprising the following steps:

[0020] (1) reacting a Fe-containing ion compound, a Co-containing ion compound, and a raw material for forming a MOFs material in an organic solvent;

[0021] (2) calcining the reaction product obtained in step (1) to obtain the composite catalyst.

[0022] According to some embodiments of the preparation method of the present invention, the Fe ion-containing compound is selected from FeCl2 and / or FeCl2·4H2O.

[0023] According to some embodiments of the preparation method of the present invention, the Co-containing ion compound is selected from Co(NO3)2 and / or Co(NO3)2·6H2O.

[0024] According to some embodiments of the preparation method of the present invention, the raw materials for forming the MOFs material include a metal salt compound and a ligand compound.

[0025] According to some embodiments of the preparation method of the present invention, the metal salt compound is selected from zinc salts.

[0026] According to some embodiments of the preparation method of the present invention, the ligand compound is 2-methylimidazole.

[0027] According to some embodiments of the preparation method of the present invention, the MOFs material is a zeolite imidazolate framework structure material, preferably ZIF-8.

[0028] According to some embodiments of the preparation method of the present invention, the organic solvent is selected from C1-C5 alcohols, preferably methanol.

[0029] According to some embodiments of the preparation method of the present invention, the molar ratio of Fe ions to MOFs materials in the Fe-ion-containing compound is (0.8-1.2):64; for example, 0.8:64, 0.9:64, 1:64, 1.2:64.

[0030] According to some embodiments of the preparation method of the present invention, the molar ratio of Co ions to MOFs materials in the Co ion-containing compound is (0.8-1.2):64; for example, 0.8:64, 0.9:64, 1:64, 1.2:64.

[0031] According to some embodiments of the preparation method of the present invention, the mass ratio of the organic solvent to the MOFs material is (3-6):1; for example, 3:1, 4:1, 5:1, 6:1.

[0032] According to some embodiments of the preparation method of the present invention, in step (1), the reaction temperature is 100-140°C; for example, 100°C, 105°C, 110°C, 120°C, 130°C, 140°C.

[0033] According to some embodiments of the preparation method of the present invention, the reaction time is 10-14 h; for example, 10 h, 11 h, 12 h, 13 h, 14 h.

[0034] According to some embodiments of the preparation method of the present invention, the reaction product obtained in step (1) is sequentially washed, dried, ground, and then calcined. According to some embodiments of the preparation method of the present invention, the washing agent used in the washing is N,N-dimethylformamide.

[0035] According to some embodiments of the preparation method of the present invention, the drying temperature is 50-70°C; for example, 50°C, 60°C, 65°C, 70°C.

[0036] According to some embodiments of the preparation method of the present invention, the drying time is 10-14 hours; for example, 10 hours, 12 hours, 13 hours, 14 hours.

[0037] According to some embodiments of the preparation method of the present invention, in step (2), the calcination is performed under an inert atmosphere.

[0038] According to some embodiments of the preparation method of the present invention, the inert atmosphere is an argon atmosphere.

[0039] According to some embodiments of the preparation method of the present invention, the calcination temperature is 800-1000°C; for example, 800°C, 900°C, 950°C, 1000°C.

[0040] According to some embodiments of the preparation method of the present invention, the calcination time is 3-6 hours; for example, 3 hours, 4 hours, 5 hours, 6 hours.

[0041] According to some embodiments of the preparation method of the present invention, the preparation method of the composite catalyst comprises the following steps:

[0042] (1) 2-methylimidazole and methanol are mixed to prepare solution A;

[0043] (2) Zn(NO3)2·6H2O, FeCl2·4H2O and Co(NO3)2·6H2O were mixed with methanol to prepare solution B;

[0044] (3) respectively subjecting solution A and solution B to ultrasonic treatment and mixing them for reaction;

[0045] (4) calcining the reaction product obtained in step (3) to obtain the composite catalyst.

[0046] The third aspect of the present invention provides an application of the composite catalyst described in the first aspect of the present invention or the composite catalyst obtained by the preparation method described in the second aspect of the present invention in treating wastewater containing organic pollutants.

[0047] According to some embodiments of the application of the present invention, the treatment method adopted is an electro-Fenton wastewater treatment method.

[0048] According to some embodiments of the application of the present invention, the organic pollutant is selected from one or more of phthalates, 2,4-dichlorophenol, bisphenol A and quinoline. According to some embodiments of the application of the present invention, the phthalates include one or more of dioctyl phthalate, dibutyl phthalate, dipentyl phthalate, diphenyl phthalate, octyl phthalate, didecyl phthalate and dimethyl phthalate; preferably dimethyl phthalate.

[0049] According to some embodiments of the application of the present invention, there is provided an application of the composite catalyst described in the first aspect of the present invention or the composite catalyst obtained by the preparation method described in the second aspect of the present invention in treating wastewater containing organic pollutants, wherein the organic pollutants are phthalates.

[0050] According to some embodiments of the application of the present invention, there is provided an application of the composite catalyst described in the first aspect of the present invention or the composite catalyst obtained by the preparation method described in the second aspect of the present invention in treating wastewater containing organic pollutants, wherein the organic pollutant is dimethyl phthalate.

[0051] A fourth aspect of the present invention provides a method for treating wastewater containing organic pollutants, comprising the following steps:

[0052] The composite catalyst described in the first aspect of the present invention or the composite catalyst obtained by the preparation method described in the second aspect of the present invention is contacted with wastewater containing organic pollutants, an electrolyte is added, and an anode and a cathode are placed therein to carry out an electro-Fenton catalytic reaction to complete the treatment of the wastewater containing organic pollutants.

[0053] According to some embodiments of the method of the present invention, the electro-Fenton catalytic reaction is carried out under the condition of continuous oxygen flow.

[0054] According to some embodiments of the method of the present invention, the oxygen gas flow rate is 25-35 sccm; for example, 25 sccm, 28 sccm, 30 sccm, 32 sccm, 35 sccm.

[0055] According to some embodiments of the method of the present invention, the electrolyte is a sodium sulfate solution.

[0056] According to some embodiments of the method of the present invention, the mass concentration of the sodium sulfate solution is 0.04-0.06 mol / L; for example, 0.04 mol / L, 0.045 mol / L, 0.05 mol / L, 0.055 mol / L, 0.06 mol / L.

[0057] According to some embodiments of the method of the present invention, the organic pollutant is selected from one or more of phthalates, 2,4-dichlorophenol, bisphenol A and quinoline; preferably phthalates.

[0058] According to some embodiments of the method of the present invention, the phthalate ester is selected from dimethyl phthalate.

[0059] According to some embodiments of the method of the present invention, the organic pollutant is selected from dimethyl phthalate.

[0060] According to some embodiments of the method of the present invention, the amount of the composite catalyst added is 2-3 mg / cm 3 ; For example, 2mg / cm 3 , 2.5mg / cm 3 、3mg / cm 3 .

[0061] According to some embodiments of the method of the present invention, the initial concentration of organic pollutants in the wastewater containing organic pollutants is 4-6 mg / L; for example, 4 mg / L, 4.5 mg / L, 5 mg / L, 5.5 mg / L, 6 mg / L.

[0062] According to some embodiments of the method of the present invention, the pH value of the wastewater containing organic pollutants is 3-9; for example, the pH value is 3, the pH value is 6, the pH value is 8, and the pH value is 9.

[0063] According to some embodiments of the method of the present invention, the voltage of the reaction system during the electro-Fenton catalytic reaction is 0.5-0.9V; for example, 0.5V, 0.6V, 0.8V, 0.9V.

[0064] According to some embodiments of the method of the present invention, the time of the electro-Fenton catalytic reaction is 4-6 hours; for example, 4 hours, 5 hours, 6 hours.

[0065] The beneficial effects of the present invention include:

[0066] (1) The iron and cobalt doped into the carbon-based material in the composite catalyst of the present invention are distributed in the form of atomic dispersion, and form a coordination structure of metal nitrogen and metal carbon, which can promote the generation of highly active oxidative species and improve the ORR performance and electron transfer ability of the material to a certain extent.

[0067] (2) The composite catalyst of the present invention has more active sites and a charge transfer resistance lower than that of the NPC catalyst. It has good electron transfer ability and high catalytic activity, can significantly reduce the toxicity of catalytic degradation products, and has high cycle stability.

[0068] (3) The composite catalyst of the present invention has a wide pH adaptability range and a degradation rate of DMP of 93.1% within 5 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1 The present invention is a flow chart of the preparation of the composite catalyst according to the embodiment of the present invention;

[0070] Figure 2a This is a scanning electron microscope image of the composite catalyst prepared in Example 1 of the present invention;

[0071] Figure 2b This is the scanning electron microscope image of the catalyst Fe@NPC;

[0072] Figure 2c This is the scanning electron microscope image of the catalyst Co@NPC;

[0073] Figure 2d This is the scanning electron microscope image of the catalyst NPC;

[0074] Figure 2e This is a TEM image of the composite catalyst prepared in Example 1 of the present invention;

[0075] Figure 2f This is the HAADF diagram of the composite catalyst prepared in Example 1 of the present invention;

[0076] Figure 2g This is an element mapping surface spectrum of the composite catalyst prepared in Example 1 of the present invention;

[0077] Figure 2h This is the elemental energy spectrum of the composite catalyst prepared in Example 1 of the present invention;

[0078] Figure 3 XANES spectra, Fourier transform EXAFS spectra of the composite catalyst, Fe foil, FeO, Fe2O3, Co foil and CoO of Example 1 of the present invention, and R space fitting curve diagram of Fe and Co in the composite catalyst;

[0079] Wherein, a is the XANES spectrum of the standardized composite catalyst, Fe foil, FeO and Fe2O3 prepared in Example 1 of the present invention; b is the Fourier transform EXAFS spectrum of the composite catalyst, Fe foil, FeO and Fe2O3 prepared in Example 1 of the present invention; c is the R space fitting curve of Fe of the composite catalyst prepared in Example 1 of the present invention; d is the XANES spectrum of the standardized composite catalyst, Co foil and CoO prepared in Example 1 of the present invention; e is the Fourier transform EXAFS spectrum of the standardized composite catalyst, Co foil and CoO prepared in Example 1 of the present invention; f is the R space fitting curve of Co of the composite catalyst prepared in Example 1 of the present invention;

[0080] Figure 4 It is a wavelet variation diagram of Fe, Fe foil, FeO and Fe2O3 in the composite catalyst of Example 1 of the present invention;

[0081] Among them, a is the wavelet change diagram of Fe in the composite catalyst prepared in Example 1 of the present invention; b is the wavelet change diagram of Fe foil prepared in Example 1 of the present invention; c is the wavelet change diagram of FeO prepared in Example 1 of the present invention; d is the wavelet change diagram of Fe2O3 prepared in Example 1 of the present invention;

[0082] Figure 5 This is a wavelet variation diagram of Co, Co foil and CoO in the composite catalyst of Example 1 of the present invention;

[0083] Among them, a is the wavelet variation diagram of Co in the composite catalyst prepared in Example 1 of the present invention; b is the wavelet variation diagram of Co foil prepared in Example 1 of the present invention; c is the wavelet variation diagram of CoO prepared in Example 1 of the present invention;

[0084] Figure 6 Electrochemical impedance spectra, cyclic voltammetry (CV) curves, LSV curves, and H2O2 selectivity and electron transfer diagrams of different catalysts;

[0085] Among them, a is the electrochemical impedance spectrum of different catalysts; b is the cyclic voltammetry (CV) curve of different catalysts measured using a single electrolytic cell; c is the LSV curve of different catalysts in O2 saturated solution (solid line part) and Ar saturated solution (dashed line part); d is the H2O2 selectivity and electron transfer diagram of different catalysts;

[0086] Figure 7 The kinetic curve diagram of the catalytic effect of the catalyst described in Example 2 of the present invention at different pH values;

[0087] Figure 8 The kinetic curve diagram of the catalytic effect of the catalyst described in Example 2 of the present invention at different voltages;

[0088] Fig. 9 It is a kinetic curve diagram of the catalytic effect of different catalysts;

[0089] Fig.10 This is a prediction diagram of the toxicity of intermediate products in the process of degrading DMP using the composite catalyst described in Example 2 of the present invention. DETAILED DESCRIPTION

[0090] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.

[0091] Example 1

[0092] First, 5.256 g of 2-methylimidazole was weighed using an electronic balance and dissolved in 80 mL of methanol to prepare solution A; solution B was prepared by dissolving 4.760 g of Zn(NO3)2·6H2O, 1 mmol / L FeCl2·4H2O and Co(NO3)2·6H2O in 120 mL of methanol solution;

[0093] Then, solution A and solution B were ultrasonicated for 10 minutes and then placed on a magnetic stirrer for mixing for 30 minutes. The mixed solution was then placed in a 300 mL Teflon reactor for hydrothermal reaction at 120°C for 4 hours. After the reaction was completed, the reaction product was washed five times with N,N-dimethylformamide and then dried in a vacuum oven at 60°C for 12 hours to obtain the precursor NPC.

[0094] Finally, the dried precursor was ground evenly, then placed in a crucible and put into a tube furnace (900°C, constant temperature for 4h) for calcination. Inert gas (argon) was continuously introduced during the entire calcination process. After completion, an iron-cobalt bimetallic doped carbon-based composite catalyst (FeCo@NPC) was obtained. The pore size of the obtained FeCo@NPC was 1.3-16nm, and the specific surface area and pore volume were 223.26m 2 / g and 0.392cm 3 / g.

[0095] The preparation method of the catalyst Fe@NPC is as follows: first, 5.256 g of 2-methylimidazole is weighed using an electronic balance and dissolved in 80 mL of methanol to prepare solution A; solution B is prepared by dissolving 4.760 g of Zn(NO3)2·6H2O and 1 mmol / L FeCl2·4H2O in 120 mL of methanol solution; the remaining operation steps are the same as the preparation method of the above-mentioned FeCo@NPC.

[0096] The preparation method of the catalyst Co@NPC is as follows: first, 5.256 g of 2-methylimidazole is weighed using an electronic balance and dissolved in 80 mL of methanol to prepare solution A; solution B is prepared by dissolving 4.760 g of Zn(NO3)2·6H2O and 1 mmol / L Co(NO3)2·6H2O in 120 mL of methanol solution; the remaining operation steps are the same as the above-mentioned preparation method of FeCo@NPC.

[0097] The specific process is as follows Figure 1 shown.

[0098] 1.1 The scanning electron microscope image of the composite catalyst FeCo@NPC prepared in this example is as follows Figure 2a As shown: The scanning electron microscopy images of Fe@NPC catalyst doped with single metal Fe, Co@NPC catalyst doped with single metal Co and NPC are shown as follows: Figure 2b , Figure 2c , Figure 2d As shown;

[0099] From Figure 2a It can be seen that the composite catalyst FeCo@NPC of the present invention retains the original cubic crystal structure.

[0100] 1.2 The TEM image and HAADF image of the composite catalyst FeCo@NPC prepared in this example are shown in Figure 2e , 2f As shown:

[0101] from Figure 2e and Figure 2f It can be seen that no metal ion-related nanoparticles were observed in the composite catalyst FeCo@NPC of the present invention.

[0102] 1.3 The element mapping spectrum of the composite catalyst FeCo@NPC prepared in this example is as follows Figure 2g The element energy spectrum is shown in Figure 2h As shown in Figure 2, the normalized X-ray absorption near edge spectra (XANES) of the composite catalyst FeCo@NPC and the standard samples (Fe foil, FeO and Fe2O3) are as follows: Figure 3As shown in a, the Fourier transform extended X-ray absorption fine structure (FE-EXAFS) of Fe in the composite catalyst FeCo@NPC is shown in Figure 3 As shown in b, the fitting curve of R space is Figure 3 c shows the normalized X-ray absorption near edge spectrum (XANES) of the composite catalyst standard (Co foil and CoO) Figure 3 d, the Fourier transform EXAFS spectra of FeCo@NPC, Co foil and CoO are shown in Figure 3 As shown in e, the R space fitting curve of FeCo@NPC catalyst Co is as follows Figure 3 f, the wavelet variation diagrams of Fe in the composite catalyst and the standard samples (Fe foil, FeO and Fe2O3) are shown as follows: Figure 4 a- Figure 4 d shows the wavelet variation of Co in the composite catalyst and the standard sample (Co foil and CoO) as shown in Figure 5 a- Figure 5 c:

[0103] from Figure 2g and Figure 2h It can be seen that the C, N, O, Fe, and Co elements in the composite catalyst (FeCo@NPC) described in this embodiment are uniformly dispersed throughout the FeCo@NPC catalyst. From the element spectrum, it can be seen that the surface doping amount of Fe and Co metals on the carbon catalyst is 0.1%. In addition, the metal doping amounts of Fe and Co detected by inductively coupled plasma (ICP-OES) are 0.7443% and 0.24%, respectively. Figure 3 As can be seen in a, the near-edge absorption intensity of Fe in FeCo@NPC is between that of FeO and Fe2O3, indicating that the valence state of the iron atoms in FeCo@NPC is between +2 and +3. Figure 3 It can be found that the iron atoms on FeCo@NPC are There is a main peak at , which should be attributed to Fe-N coordination. Figure 3 As shown in d, the near-edge absorption intensity of Co is between that of CoO and Co foil, indicating that the cobalt atoms in FeCo@NPC carry positive charges of +2 to +3. Its FTEXAFS curve and EXAFS fitting diagram jointly reveal the Co-N coordination of cobalt atoms ( Figure 3 ef). Neither Fe nor Co in FeCo@NPC has Fe-Fe and Co-Co related peaks. Figure 4 Wavelet variation diagram of catalysts FeCo@NPC, Fe foil, FeO and Fe2O3. Figure 4 The wavelet variation contour map (WT contour map) of the iron foil in bd shows the existence of Fe-Fe bonds Iron Oxide Fe-O Bond and Fe-O bonds These two bond types do not exist on FeCo@NPC, which should be attributed to Fe-N coordination. This result is similar to the structure of its Fourier transform expansion. Figure 5 The wavelet variation diagram of the catalysts FeCo@NPC, Co foil and CoO shows that there is no Co-Co in FeCo@NPC. and Co-O The bond type of Co-N and Co-C coordination was found in the WT contour diagram. The above results indicate that Fe and Co metals exist in the catalyst in the form of atoms.

[0104] Application Example 1

[0105] Using an electrochemical workstation, the four catalysts of NPC, Co@NPC, Fe@NPC and the composite catalyst (FeCo@NPC) described in Example 1 were charged at 0.625 mg / cm 2 The density was loaded on a carbon paper of 2cm×2cm×0.1cm, and the electrochemical performance was measured in 0.05M Na2SO4 solution.

[0106] NPC refers to: the precursor prepared in Example 1;

[0107] Co@NPC means: cobalt-doped porous carbon;

[0108] Fe@NPC means: iron-doped porous carbon;

[0109] The electrochemical impedance spectroscopy (EIS) of the four catalysts was tested in a Na2SO4 electrolyte using a three-chamber electrolytic cell. Figure 6 As shown in a;

[0110] Combined with the rotating ring disk experiment (RRDE), Figure 6 It can be seen from a that the catalyst after metal doping has higher hydrogen peroxide selectivity and good electron transfer ability.

[0111] The redox reaction capabilities of the four catalysts were tested using cyclic voltammetry (CV) curves measured by a single electrolytic cell. Figure 6 As shown in b;

[0112] The LSV curves of the four catalysts in O2 saturated solution and Ar saturated solution were tested. The results are shown in Figure 6 As shown in c;

[0113] The electron transfer ability of the four catalysts was studied by linear sweep voltammetry (LSV); the results are shown in Figure 6 As shown in d;

[0114] from Figure 6 b- Figure 6 As can be seen in d, the starting potential of the catalyst NPC is 0.018 V and the current density is 3.91 mV / cm -2 , while the starting potential of Co@NPC is 0.095 V, and the current density is 4.17 mV / cm -2 The starting potential of Fe@NPC is 0.138 V and the current density is 7.48 mV / cm -2 The starting potential of FeCo@NPC is 0.081V, and the current density is 4.62mA / cm -2 All three exhibited more positive ORR starting potentials and higher ORR current densities. Moreover, combined with the rotating ring disk experiment (RRDE), it was found that the catalysts doped with metals had higher hydrogen peroxide selectivity and good electron transfer ability. Figure 6 d.

[0115] Example 2

[0116] First, 5.256 g of 2-methylimidazole was weighed using an electronic balance and dissolved in 80 mL of methanol to prepare solution A; 4.760 g of Zn(NO3)2·6H2O was weighed and dissolved in 120 mL of methanol solution to prepare solution B;

[0117] Then, solution A and solution B were ultrasonicated for 10 minutes and then placed on a magnetic stirrer for mixing for 30 minutes. The mixed solution was then placed in a 200 mL Teflon reactor for hydrothermal reaction at 120°C for 4 hours, and the reaction product was washed five times with methanol and DMF, and then dried in a vacuum oven at 60°C for 12 hours to obtain a precursor;

[0118] Finally, the dried precursor was ground evenly, then placed in a crucible and put into a tube furnace (900°C, constant temperature for 4h) for calcination. Inert gas (argon) was continuously introduced during the entire calcination process. After completion, an iron-cobalt bimetallic doped carbon-based composite catalyst (FeCo@NPC) was obtained. The pore size of the obtained FeCo@NPC was 1.3-16nm, and the specific surface area and pore volume were 223.26m 2 / g and 0.392cm 3 / g.

[0119] Application Example 2

[0120] An electrochemical workstation (CHI 760e) was used to evaluate the degradation performance of FeCo@NPC prepared in Example 2 by the heterogeneous electro-Fenton process on DMP. The degradation process of DMP was carried out in a three-cell reactor with a continuous flow of O2 at a flow rate of 30 sccm, and the electrolyte was a 0.05 M sodium sulfate solution.

[0121] 2.1 The effect of different pH values ​​on the catalytic degradation effect is shown in Table 1. The kinetic curve is shown in Figure 7 As shown:

[0122] Table 1 Degradation effect under different pH conditions

[0123]

[0124] Note: The voltage of the reaction is 0.7v and the initial concentration of organic pollutants is 5mg / L.

[0125] It can be seen from Table 1 that when the pH value is 7, the degradation effect of DMP is the best, reaching 93.1%; but a closer look shows that under the catalyst modification, the effect of pH on the reaction is not as great as that of homogeneous electro-Fenton, and can reach more than 80% under neutral and slightly alkaline conditions.

[0126] from Figure 7 It can be seen that the degradation effect at pH = 7 also conforms to the first-order kinetic reaction, and its reaction efficiency is relatively close to that at pH = 3, that is, the heterogeneous electro-Fenton system modified by FeCo@NPC is little affected by pH, which further illustrates that the composite catalyst described in this application can be used in more complex and changing environments.

[0127] 2.2 Effect of different voltages on catalytic degradation. The results are shown in Table 2. The kinetic curves are shown in Figure 8 As shown:

[0128] Table 2 Effect of different voltages on catalytic degradation

[0129]

[0130] Note: The pH of the wastewater to be degraded in this reaction is 7, and the initial concentration of organic pollutants is 5 mg / L.

[0131] It can be seen from Table 2 that when the applied voltage is increased from -0.5V (vs. SCE) to -0.9V (vs. SCE), it is found that the degradation rates at -0.7V and -0.5V are similar, both above 90%, but the degradation of DMP is slightly lower when the voltage is -0.9V, and from the kinetic curve ( Figure 8 ) It can be seen that the reaction rate is faster when V = -0.7V.

[0132] 2.3 Study on the catalytic degradation effect of different catalysts. The results are shown in Table 3. The kinetic curves are shown in Fig. 9 As shown:

[0133] Table 3 Study on the catalytic degradation effect of different catalysts

[0134]

[0135] Note: In this reaction, the pH of the wastewater to be degraded is 7, the voltage is -0.7 V, and the initial concentration of organic pollutants is 5 mg / L.

[0136] It can be seen from Table 3 that FeCo@NPC has the best degradation activity for DMP, with a removal rate of 93% within 5 h, which is significantly higher than the NPC removal rate of 37%, Co@NPC removal rate of 70% and Fe@NPC removal rate of 77% under the same conditions.

[0137] from Fig. 9 It can be seen that the degradation of FeCo@NPC catalyst is more consistent with the first-order kinetic reaction, and its reaction rate NPC (0.19h -1 ) <Co@NPC(0.24h -1 ) <Fe@NPC(0.29h -1 ) <FeCo@NPC(0.53h -1 ). That is, the heterogeneous electro-Fenton system modified with FeCo@NPC has better degradation performance than the other four catalysts.

[0138] 2.4 The degradation effect of the composite catalyst described in this example on common refractory organic pollutants was studied. The results are shown in Table 4:

[0139] Table 4 Study on the degradation effect of different difficult-to-degrade organic pollutants

[0140]

[0141] Note: The pH of the wastewater to be degraded in this reaction is 7, the voltage is -0.7V, and the initial concentration of organic pollutants is 5mg / L.

[0142] It can be seen from Table 4 that the catalyst described in the present application has a high degradation rate for DMP, 2,4-dichlorophenol, bisphenol A and quinoline. The degradation rate for 2,4-dichlorophenol reaches 95%, the degradation rate for quinoline reaches 89%, and the degradation rate for bisphenol A reaches 100%. That is, the FeCo@NPC catalyst has a high removal effect on various difficult-to-degrade organic pollutants.

[0143] 2.5 The repeated use stability study of the composite catalyst, the results are shown in Table 5 (the specific operation method is the same as that of Application Example 2):

[0144] Table 5 Study on the repeated use stability of the composite catalyst

[0145]

[0146] It can be seen from Table 5 that when the heterogeneous electro-Fenton system constructed by FeCo@NPC was repeated for the fourth time, the degradation rate of DMP reached 77.8%, and basically showed a balanced trend, that is, the composite catalyst of the present invention still had a high catalytic activity after multiple repetitions.

[0147] 2.6 Study on the toxicity of intermediate products in the process of DMP degradation by the composite catalyst described in this application

[0148] Research method: The prediction was performed using the ECOSAR program. The results are as follows: Fig.10 shown.

[0149] from Fig.10 It can be seen that DMP has a relatively high toxicity both acutely and chronically. After degradation, its toxicity can be reduced or even become non-toxic.

[0150] Among them, the acute toxicity of DMP to fish, water flea and green algae is 37.4mg / L, 89.9mg / L and 47.8mg / L respectively. The final product after degradation is basically non-toxic to fish, water flea and green algae.

[0151] In terms of chronic toxicity, the chronic toxicity of DMP to fish, daphnia and green algae are 2.33 mg / L, 11.7 mg / L and 14.2 mg / L respectively. The final products and intermediate products after degradation are basically non-toxic to fish, daphnia and green algae.

[0152] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite catalyst having a cubic crystal structure, comprising a MOFs material and iron atoms and cobalt atoms doped in the MOFs material; Preferably, the pore size of the composite catalyst is 3-20 nm; Preferably, the specific surface area of ​​the composite catalyst is 150-250m 2 / g, preferably 154-225m 2 / g; Preferably, the pore volume of the composite catalyst is 0.2-0.5 cm 3 / g, preferably 0.25-0.4cm 3 / g.

2. The catalyst according to claim 1, characterized in that The MOFs material is a zeolite imidazolate framework structure material; Preferably, the zeolite imidazolate framework material is ZIF-8; and / or, the molar ratio of the MOFs material to the iron atom is 64:(0.8-1.2); and / or, the molar ratio of the MOFs material to the cobalt atom is 64:(0.8-1.2); And / or, the molar ratio of the iron atoms to the cobalt atoms is 1:(0.8-1.2).

3. The method for preparing the composite catalyst according to claim 1 or 2, comprising the following steps: (1) reacting a Fe-containing ion compound, a Co-containing ion compound, and a raw material for forming a MOFs material in an organic solvent; (2) calcining the reaction product obtained in step (1) to obtain the composite catalyst.

4. The preparation method according to claim 3, characterized in that: The Fe-ion-containing compound is selected from FeCl2 and / or FeCl2·4H2O; and / or, the Co-containing ion compound is selected from Co(NO3)2 and / or Co(NO3)2·6H2O; And / or, the raw materials for forming the MOFs material include a metal salt compound and a ligand compound, preferably the metal salt compound is selected from zinc salts, and / or preferably the ligand compound is 2-methylimidazole; And / or, the MOFs material is a zeolite imidazolate framework material, preferably ZIF-8; And / or, the organic solvent is selected from C1-C5 alcohols, preferably methanol; And / or, the molar ratio of Fe ions to MOFs materials in the Fe ion-containing compound is (0.8-1.2):64; And / or, the molar ratio of Co ions to MOFs materials in the Co ion-containing compound is (0.8-1.2):64; And / or, the mass ratio of the organic solvent to the MOFs material is (3-6):

1.

5. The preparation method according to claim 3 or 4, characterized in that: In step (1), the reaction temperature is 100-140°C; And / or, the reaction time is 10-14h; and / or, the reaction product obtained in step (1) is sequentially washed, dried, ground, and then calcined; Preferably, the washing agent used in the washing is N,N-dimethylformamide; Preferably, the drying temperature is 50-70°C, more preferably, the drying time is 10-14h; And / or, in step (2), the calcination is carried out under an inert atmosphere, preferably, the inert atmosphere is an argon atmosphere; And / or, the calcination temperature is 800-1000°C; And / or, the calcination time is 3-6h.

6. Use of the composite catalyst according to any one of claims 1 to 2 or the composite catalyst obtained by the preparation method according to any one of claims 3 to 5 in treating wastewater containing organic pollutants.

7. The use according to claim 6, characterized in that: The method adopted for the treatment is the electro-Fenton sewage treatment method; Preferably, the organic pollutant is selected from one or more of phthalates, 2,4-dichlorophenol, bisphenol A and quinoline; Preferably, the phthalate ester includes one or more of dioctyl phthalate, dibutyl phthalate, dipentyl phthalate, diphenyl phthalate, octyl phthalate, didecyl phthalate and dimethyl phthalate; preferably dimethyl phthalate.

8. A method for treating wastewater containing organic pollutants, comprising the following steps: The composite catalyst described in any one of claims 1-2 or the composite catalyst obtained by the preparation method described in any one of claims 3-5 is contacted with wastewater containing organic pollutants, an electrolyte is added, and an anode and a cathode are placed therein to carry out an electro-Fenton catalytic reaction to complete the treatment of the wastewater containing organic pollutants.

9. The method according to claim 8, characterized in that The electro-Fenton catalytic reaction is carried out under the condition of continuous oxygen flow; preferably, the oxygen flow rate is 25-35 sccm; And / or, the electrolyte is a sodium sulfate solution; preferably, the mass concentration of the sodium sulfate solution is 0.04-0.06 mol / L; And / or, the organic pollutant is selected from one or more of phthalates, 2,4-dichlorophenol, bisphenol A and quinoline; preferably phthalates; preferably, the phthalates are selected from dimethyl phthalate; And / or, the addition amount of the composite catalyst is 2-3 mg / cm 3 ; and / or, the initial concentration of organic pollutants in the wastewater containing organic pollutants is 4-6 mg / L; And / or, the pH value of the wastewater containing organic pollutants is 3-9.

10. The method according to claim 8 or 9, characterized in that: The voltage of the reaction system during the electro-Fenton catalytic reaction is 0.5-0.9V; And / or, the electro-Fenton catalytic reaction time is 4-6h.